Care in Healthcare : Reflections on Theory and Practice - Krause, Franziska; Boldt, Joachim; Krause, Franziska; Boldt, Joachim (Basingstoke Springer Nature, 2017)
medical ethics; healthcare; nursing; midwifery
English
Keywords: Medical ethics & professional conduct; medical ethics; healthcare; nursing; midwifery